Biomass briquetting: a training module for trainers and practitioners - Somorin, Tosin; Gitau, J.; Agbefu, Dzifa; Gebrezgabher, Solomie A. (International Water Management Institute (IWMI). CGIAR Initiative on Nature-Positive Solutions, 2023)
This training manual was primarily designed to support the training of small-scale farmers and entrepreneurs on how to produce biomass briquettes from agricultural wastes and residues. Part 1 introduces key concepts in biomass briquette production and the benefits that may be realised. Further information on process parameters is also provided e.g., how operating conditions affect the quality and performance of biomass briquettes; what waste types, binders, and technologies are appropriate for biomass briquetting and the key safety considerations to be put in place to ensure a safe and sustainable enterprise. Part 2 provides step-by-step guidance on ‘how-to processes e.g., how to produce briquettes from different biomass or waste streams using carbonisation and non-carbonisation methods and how to use briquettes for fuel and other energy purposes safely. The manual was made available by CGIAR initiative on Nature-Positive Solutions (NATURE+). The training manual can be adapted as an operational or train-the-trainer manual for training community groups, enterprises, individuals, and organizations working or interested in waste management, circular economy, or renewable energy, particularly women and youth. No prior understanding is necessary although a basic background in natural sciences may be useful. Technical training may be facilitated with practical demonstrations.